2013
DOI: 10.1080/17445302.2013.793122
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of dynamic behaviour of high-speed catamaran craft subjected to underwater explosion

Abstract: In recent years, shock trials for surface ships have been conducted in many countries for qualification of ship integrity, systems and subsystems in response to shock. A ship trial identifies design and construction deficiencies that negatively impact ship and crew survivability. Such a trial also validates shock hardening and performance of shipboard equipments. However, livefire ship shock trials and underwater explosion testing are both complex and expensive. As a possible alternative, numerical modelling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Prusty et al [31] and Gupta et al [28] are good examples of the precision with which FEM models can reproduce the response of metallic stiffened panels to UNDEX. Also, FEM constitutes the best technique through which the hull girder strength can be assessed by a progressive collapse analysis and its consequent non-linearity [56], as Chung et al [58] demonstrated by evaluating the structural response of a catamaran, even taking into account the strain rate effects of the material. Not confined to monolithic structures, Tillbrook et al [37] demonstrated that beams made of sandwich material compositions can have their dynamic response to UNDEX adequately described by FEM, which is a recognized standard approach to model ship structures by naval classification agencies and the navy [59].…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Prusty et al [31] and Gupta et al [28] are good examples of the precision with which FEM models can reproduce the response of metallic stiffened panels to UNDEX. Also, FEM constitutes the best technique through which the hull girder strength can be assessed by a progressive collapse analysis and its consequent non-linearity [56], as Chung et al [58] demonstrated by evaluating the structural response of a catamaran, even taking into account the strain rate effects of the material. Not confined to monolithic structures, Tillbrook et al [37] demonstrated that beams made of sandwich material compositions can have their dynamic response to UNDEX adequately described by FEM, which is a recognized standard approach to model ship structures by naval classification agencies and the navy [59].…”
Section: Numerical Modellingmentioning
confidence: 99%
“…By comparing the structural resistance results of model simulation under experimental conditions with the results of model experiments, the effectiveness of the numerical method was validated. Chung et al [39] took a high-speed catamaran as an example, conducted impact modeling of the catamaran ship type and fluid model based on the finite element method, proposed an impact resistance analysis method for high-speed catamaran ship types and discussed related influencing parameters, and finally compared the simulation results with empirical data for analysis. Sigrist et al [40] proposed a universal method for analyzing the dynamic response of underwater impact loads on ship equipment without the need for 'coupled calculations'.…”
Section: Introductionmentioning
confidence: 99%